IgE sensitization in a cohort of adolescents in southern Sweden and its relation to allergic symptoms - Sterner, Therese (Clin Mol Allergy, 2019)
BACKGROUND: There is a strong and consistent association between IgE sensitization and allergy, wheeze, eczema and food hypersensitivity. These conditions are also found in non-sensitized humans, and sensitization is found among individuals without allergy-related diseases. The aim of this study was to analyse the sensitization profile in a representative sample of the population, and to relate patterns of allergens and allergen components to allergic symptoms. METHODS: A population of 195 adolescents took part in this clinical study, which included a self-reported questionnaire and in vitro IgE testing. RESULTS: Sensitization to airborne allergens was significantly more common than sensitization to food allergens, 43% vs. 14%, respectively. IgE response was significantly higher in airborne allergens among adolescents with rhinitis (p < 0.001) and eczema (p < 0.01). Among 53 children with allergic symptoms according to the questionnaire, 60% were sensitized. Sensitization to food allergens was found among those with rhinitis, but only to PR-10 proteins. None of the participants had IgE to seed storage proteins. CONCLUSION: The adolescents in this study, taken from a normal Swedish population, were mainly sensitized to grass pollen and rarely to specific food allergens. The major grass pollen allergen Phl p 1 was the main sensitizer, followed by Cyn d 1 and Phl p 2. Sixty-one percent reporting any allergic symptom were sensitized, and the allergen components associated with wheeze and rhinoconjunctivitis were Fel d 4, Der f 2 and Can f 5.